51 - SOMATIC PARAMETERS AND PHYSICAL FITNESS LEVEL DETERMINATION BY PHYSICAL ACTIVITY ATTITUDES OF SLOVAK UNIVERSITY STUDENTS (Fiep Bulletin - online, 2023)
Introduction: Regular whole life recreational movement activity plays irreplaceable role for increasing individual health and prolonging active life. From the point of the view the childhood and adolescent age are the decisive periods for performing physical activities and its integration into life of each man. University students are specific and numerous social groups. Hey are in critical age from the point of performing recreational activities and thus their physical fitness level can often decrease. In this contribution authors deal with relationships of physical activity attitudes with somatic and physical fitness parameters of Slovak universities students. Material and methods: In this research are involved 606 students, 344 males and 262 females from two Bratislava Universities (8 faculties). Attitudes were estimated by Lickert scale in three components (cognitive, emotional and tendency to act), from somatic parameters were measured body height and body weight, physical fitness was evaluated with reduced Eurofit and former Czechoslovak battery tests: sit and reach, standing broad jump, medicine ball throw, shuttle run 10x5m, sit-ups and endurance shuttle run. We have available students from the Faculty of Physical Education and Sports (FSPORT) and from 8 different faculties (not physical education and sport study orientation). Differences and relationships were evaluated by t-test and correlative coefficients; we used •p